10.1016/s1544-8800(10)70196-2 (CrossRef Listing of Deleted DOIs, 2000)
Objective To elucidate the relationship between immediate whitening (IW), vacuole formation, and melanosome disruption in in vivo human skin following picosecond laser irradiation and to establish a mechanistic basis for clinical endpoint selection in pigmented lesions. Methods A 755-nm picosecond laser was applied to in vivo normal human skin under varying irradiation conditions. IW responses were graded clinically. Histological analysis quantified vacuole number density and area, and electron microscopy assessed melanosome morphology. A melanosome disruption threshold fluence model was used to estimate fluence at the dermoepidermal junction (DEJ) and to validate the experimental irradiation conditions. Comparisons with a 755-nm nanosecond laser were performed under endpoint-matched and DEJ fluence-matched conditions. Results Vacuole area increased with the IW degree. Under slight IW, some vacuoles exceeded the cellular scale (defined by basal cell area), whereas under no IW, vacuoles remained below the cellular scale despite melanosome disruption. These findings indicate that the spatial scale of laser-induced immediate responses shifts from subcellular (no IW) to cellular levels (slight IW). Theoretical analysis confirmed that most irradiation settings exceeded the threshold for melanosome disruption. Compared with nanosecond lasers, picosecond lasers produced more spatially confined vacuole formation at matched IW levels, but larger vacuoles under DEJ fluence-matched conditions. Conclusion IW reflects the spatial scale of picosecond laser-induced immediate responses and serves as a mechanistic indicator for disease-specific clinical endpoint selection. These findings provide a framework for optimizing and standardizing picosecond laser treatment parameters.